The influence of caudofemoral musculature on the titanosaurian (Saurischia: Sauropoda) tail skeleton: morphological and phylogenetic implications - Ibiricu, Lucio Manuel (2013)
Due to their abundance, taxonomic and morphological diversity, wide range of body sizes and broad geographical distribution, titanosaurian sauropods were one of the most important Cretaceous herbivorous dinosaur groups. Consequently, titanosaurs constitute one of the best samples in which to evaluate the relationship between bony structures and unpreserved soft-tissues within Sauropoda. We reconstruct the morphology and interpret the implications of selected soft-tissues associated with the titanosaurian caudal skeleton. These tissues, especially the M. caudofemoralis longus (CFL), exerted a considerable influence on the anatomy of the caudal vertebrae and haemal arches. In all studied titanosaurian taxa, the reconstructed caudofemoral musculature corresponds to one of three principal morphotypes that accord with previously recognised phylogenetic patterns within the clade. Basal titanosaurians had an elongate M. CFL that extended for much of the proximal half of the tail; in saltasaurines, this muscle was much shorter. Non-saltasaurine lithostrotians exhibited an intermediate condition. Furthermore, the differing position of the fourth trochanter, and therefore, the insertion of the caudofemoral muscles, among various titanosaurian taxa suggests distinctions in the locomotor function of these animals.